Incidental Finding of a Large Right Atrial Thrombus in a Patient With Cerebral Lymphoma - Ayman R. Fath MD; Abdullah S. Eldaly MBChB; Amro Aglan MBChB; Kyle S. Varkoly BS; Roxana N. Beladi BA; Anup Solsi MD; Mary F. Hahn MD; John P. Karis MD; Sina Nafisi MD, FACC; Kevin Brady MD; Pallavi Bellamkonda MD, FACC; Dara N. Wakefield MD; et al. (SAGE Publishing, 2021)
Right atrial (RA) masses are rare, challenging to diagnose, and potentially life-threatening with high mortality if untreated. We present a patient presenting with diffuse large B-cell lymphoma in the brain that was incidentally found to have a large RA mass. For a better definition of the RA mass, extensive workup using multimodality imaging including chest computed tomography, transthoracic echocardiography, transesophageal echocardiography, cardiac magnetic resonance imaging, and left heart catheterization was warranted. The imaging demonstrated a large RA mass extending through the tricuspid valve into the right ventricle and superior and inferior vena cava without a mobile component. The mass was then successfully resected, and further histology examination was performed to rule out lymphoma and rare subtypes of diffuse large B-cell lymphoma. The comprehensive workup proved the RA mass to be a calcified thrombus rather than a direct metastatic spread of lymphoma.